Newspaper reporting and the public construction of homicide - Ackerley, Elizabeth; Francis, Brian; Soothill, Keith; Pearson, Jayn (The British journal of criminology, 2004)
This paper outlines the distorted nature of press reporting of English and Welsh homicides. We investigated the reporting of 2,685 homicides in England and Wales in three national newspapers: The Times, the Mail and the Mirror in the period 1993-97. By systematically charting the nature of reporting distortions, we explore the contribution of newspapers to the social construction of homicide. The study analysed a wide range of variables to explain homicide story salience: the circumstance of the killing was found to play a crucial role in whether a homicide is reported, with sexual homicides and motiveless acts being more likely to be reported. Homicides involving young children are highly likely to be reported, but infant homicides are not. These public narratives construct homicide differently to the reality of illegal killing, highlighting particular versions of otherness' and danger. Such distorted contributions to framing criminological problems may, we argue, foster political and social responses to homicide that are not based on statistical reality but media representations of reality